Neurochemical disorders at the hypoxic-ischemic encephalopathy in newborns - Tamara Chuvakova; Bekturgan Karin (National Scientific Medical Center, 2017)
The article presents an image of the modern interpretation of the pathogenesis of hypoxic-ischemic encephalopathy in newborns, which later develops an understanding of the direction of therapeutic effects that provide a neuroprotective effect in a particular phase of the pathological process.